Phenotypic discordance in semilobar holoprosencephaly: a case report of total arhinia and median clefting linked to gestational diabetes - Janu Chhetri; Rejina Chhetri (Annals of Medicine & Surgery, 2026)
Introduction: Holoprosencephaly (HPE) is a complex spectrum of cephalic malformations resulting from incomplete prosencephalic division. Semilobar HPE is an intermediate variant, often associated with significant craniofacial dysmorphism and neurological morbidity. Case presentation: We present a preterm female infant born to a mother with unmanaged gestational diabetes. At birth, she exhibited microcephaly, total arhinia, and a median cleft lip and palate. MRI confirmed semilobar HPE. Clinical progression included hypotonia, seizures, and recurrent hyperpyrexia associated with hypothalamic dysfunction. Despite the absence of a nasal airway, the infant transitioned to reflexive mouth breathing and required long-term orogastric tube feeding. Notably, she has maintained systemic stability throughout an 8-month follow-up, facilitated by a proactive, multidisciplinary home-based care model. Discussion: This case illustrates a phenotypic discordance in which severe arhinia occurs alongside intermediate cerebral cleavage, suggesting a potential vulnerability in which nasal placode development may be highly sensitive to maternal hyperglycemia, which is hypothesized to perturb cholesterol-dependent Sonic Hedgehog signaling. Our clinical experience demonstrates that by prioritizing rigorous caloric titration and proactive monitoring of autonomic and infectious triggers, it is possible to successfully navigate the patient’s precarious equilibrium and prevent the secondary morbidity typically associated with hypothalamic instability. Conclusion: This report demonstrates that even in the presence of profound structural and autonomic vulnerabilities, proactive multidisciplinary management can effectively mitigate secondary systemic morbidity and support survival beyond the neonatal period. This approach provides a viable model for stabilizing patients with severe holoprosencephaly through consistent, home-based surveillance and functional support.